Functional connectivity changes in the language network during stroke recovery. (15th January 2015) - Nair, Veena A.; Young, Brittany M.; La, Christian; Reiter, Peter; Nadkarni, Tanvi N.; Song, Jie; Vergun, Svyatoslav; Addepally, Naga Saranya; Mylavarapu, Krishna; Swartz, Jennifer L.; Jensen, Matthew B.; Chacon, Marcus R.; et al.
Abstract Objective Several neuroimaging studies have examined language reorganization in stroke patients with aphasia. However, few studies have examined language reorganization in stroke patients without aphasia. Here, we investigated functional connectivity (FC) changes after stroke in the language network using resting‐state fMRI and performance on a verbal fluency (VF) task in patients without clinically documented language deficits. Methods Early‐stage ischemic stroke patients (N = 26) (average 5 days from onset), 14 of whom were tested at a later stage (average 4.5 months from onset), 26 age‐matched healthy control subjects (HCs), and 12 patients with cerebrovascular risk factors (patients at risk, PR) participated in this study. We examined FC of the language network with 23 seed regions based on a previous study. We evaluated patients' behavioral performance on a VF task and correlation between brain resting‐state FC (rsFC) and behavior. Results Compared to HCs, early stroke patients showed significantly decreased rsFC in the language network but no difference with respect to PR. Early stroke patients showed significant differences in performance on the VF task compared to HCs but not PR. Late‐stage patients compared to HCs and PR showed no differences in brain rsFC in the language network and significantly stronger connections compared to early‐stage patients. Behavioral differences persisted in the late stage compared to HCs. Change in specific connection strengths correlated with changes in behavior from early to late stage. Conclusions These results show decreased rsFC in the language network and verbal fluency deficits in early stroke patients without clinically documented language deficits.